2001
DOI: 10.1007/s000110050737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leukotriene B 4 receptor antagonist, LY293111Na, on antigen-induced bronchial hyperresponsiveness and leukocyte infiltration in sensitized guinea pigs

Abstract: These results indicate that LTB4 may participate in antigen-induced BHR but not in eosinophil infiltration and acute bronchoconstriction in guinea pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Pharmacological blockade of the LTB4 receptor confirmed these results as treatment with the LTB4 receptor antagonist prevented the induction of increased airway reactivity following T EFF transfer into passively sensitized and OVA-exposed CD8 Ϫ/Ϫ mice as well as in WT mice. Other antagonists of the LTB4 receptor have also been reported to suppress AHR in rodent models (49,50), consistent with the present data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pharmacological blockade of the LTB4 receptor confirmed these results as treatment with the LTB4 receptor antagonist prevented the induction of increased airway reactivity following T EFF transfer into passively sensitized and OVA-exposed CD8 Ϫ/Ϫ mice as well as in WT mice. Other antagonists of the LTB4 receptor have also been reported to suppress AHR in rodent models (49,50), consistent with the present data.…”
Section: Discussionsupporting
confidence: 92%
“…All passively sensitized and challenged WT mice (independent of the strain) showed an increased response to EFS (defined as a decrease in ES 50 ) when compared with the passively sensitized but saline-challenged or nonsensitized but allergen-challenged animals (Figs. 1, A-C).…”
Section: Development Of Increased Airway Reactivity Following Passivementioning
confidence: 99%
“…High-affinity LTB 4 receptors are on peripheral blood leukocytes as well as in the spleen and thymus, while low-affinity LTB 4 receptors are present on granulocytes and in the spleen [36]. The potent role of LTB 4 receptors in many different inflammatory diseases has led to the development of LTB 4 receptor antagonists as potential anti-inflammatory therapeutic treatments for pulmonary [37] and cutaneous [38][39][40] inflammatory states as well as immunosuppressive agents [41]. Such studies demonstrate that the LTB 4 receptor could be a potential target for therapeutic treatments for SMinduced skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports, though, have shown significant contraction of lung parenchymal strips by nanomolar concentrations of LTB 4 (24). Some studies have concluded that LTB 4 antagonists have minor effects on leukocyte accumulation but decrease bronchial hyperreactivity (25,26), another showed decreased leukocyte recruitment but no effect on pulmonary function (27), and another found that antigen-induced bronchoconstriction was decreased but eosinophil accumulation and acute bronchial hyperreactivity were unaffected (28).…”
Section: Discussionmentioning
confidence: 99%